Design, Formulation and Evaluation of Atenolol Gastro Retentive Floating Tablets - Gunda, Raghavendra Kumar (Asian Journal of Pharmaceutics (AJP), 2016)
The main objective of present research work is to formulate the floating tablets of atenolol using 32 factorial design. Atenolol, β-blocker belongs to Biopharmaceutical Classification System Class-III. The floating tablets of atenolol were prepared employing different concentrations of hydroxypropyl methylcellulose (HPMC) K15M and sodium bicarbonate in different combinations by direct compression technique using 32 factorial design. The concentration of HPMC K15M and sodium bicarbonate required to achieve desired drug release was selected as independent variables, X1 and X2, respectively, whereas time required for 10% of drug dissolution (t10%), 50% (t50%), 75% (t75%), and 90% (t90%) were selected as dependent variables. Totally, nine formulations were designed and are evaluated for hardness, friability, thickness, % drug content, floating lag time, in vitro drug release. From the results, concluded that all the formulation were found to be within the pharmacopoeial limits and the in vitro dissolution profiles of all formulations were fitted into different Kinetic models, the statistical parameters like intercept (a), slope (b) and regression coefficient (r) were calculated. Polynomial equations were developed for t10%, t50%, t75%, t90%. Validity of developed polynomial equations was verified by designing 2 checkpoint formulations (C1, C2). According to SUPAC guidelines the formulation (F8) containing combination of 25% HPMC K15M and 3.75% sodium bicarbonate, is the most similar formulation (similarity factor f2 = 87.797, dissimilarity factor f1 = 2.248 and no significant difference, t = 0.098) to marketed product (BETACARD). The selected formulation (F8) follows Higuchi’s kinetics, and the mechanism of drug release was found to be non-Fickian diffusion (n = 1.029, Super Case-II transport).